2016
DOI: 10.1002/adv.21646
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, Thermal, Morphological, and Biodegradable Studies of Okra Cellulosic Fiber Reinforced Starch‐Based Biocomposites

Abstract: ABSTRACT:The aim of present work is to study the behavior of completely biodegradable starch-based composites containing okra cellulosic fibers in the range from 5 to 25 wt%. The cornstarch matrix and composites were prepared by using urea-formaldehyde as a cross-linking agent. The cross-linked cornstarch matrix and its composites were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, X-ray diffraction, and thermogravimetric analysis. Furthermore, thermal and different mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 29 publications
1
12
0
8
Order By: Relevance
“…To that end, particular emphasis is given to natural fiber-reinforced degradable matrices, such as poly(lactic acid), poly(butylene succinate), polyhydroxybutyrate, and thermoplastic starch [2]. A range of starch-based biodegradable polymer composites have been investigated including okra-cellulosic fiber/corn starch [3], kenaf/starch [4], laver/starch [5], untreated bagasse/cassava starch [6], treated bagasse/cassava starch [7], luffa/cassava starch [8], cellulose fiber derived from newspaper/corn starch [9], wood fiber/potato starch [10], and almond shell/starch-based polymer composites [11].…”
Section: Introductionmentioning
confidence: 99%
“…To that end, particular emphasis is given to natural fiber-reinforced degradable matrices, such as poly(lactic acid), poly(butylene succinate), polyhydroxybutyrate, and thermoplastic starch [2]. A range of starch-based biodegradable polymer composites have been investigated including okra-cellulosic fiber/corn starch [3], kenaf/starch [4], laver/starch [5], untreated bagasse/cassava starch [6], treated bagasse/cassava starch [7], luffa/cassava starch [8], cellulose fiber derived from newspaper/corn starch [9], wood fiber/potato starch [10], and almond shell/starch-based polymer composites [11].…”
Section: Introductionmentioning
confidence: 99%
“…The soil burial method was used to study the biodegradability of starch films. (Bootklad & Kaewtatip, 2013;Guleria, Singha, & Rana, 2018) The samples of films (dimensions 10 mm× 10 mm× 1.5 mm) were buried in natural soil at a depth of 7 cm in Changchun, China. The temperature was maintained at 23 ± 5°C, and the relative humidity (RH) was kept in the range of 40-50%.…”
Section: Biodegradation Testmentioning
confidence: 99%
“…Mercerization modification is another chemical treatment of lignocellulosic fibers that has been applied by Guleria et al in 2017, to obtain the biocomposites based on corn starch matrix. The addition of mercerized lignocellulosic fibers to starch resulted in an enhancement in tensile, flexural and compression strength of the biocomposites 8 . Kargarzadeh et al in 2017 have shown that load transfer efficiency from cassava starch matrix to reinforcing fibers improves by the chemical modification of lignocellulosic fibers, owing to better matrix/filler adhesion caused by the removal of non‐cellulosic constituents of lignocellulosic fibers 9 .…”
Section: Introductionmentioning
confidence: 99%